COVID-19 and inequality - Sarra Ben Yahmed; Lorenzo Cappellari; Daniele Checchi; Miles Corak; Stephen P. Jenkins; Guido Neidhöfer; Michele Tertilt; Mariano Tommasi (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
The COVID-19 pandemic and the socially distanced economy reveal longstanding inequalities that have been growing wider and wider for decades. This Policy Brief summarizes and contextualizes some of the main results of the Webinar "COVID-19 and Inequality: Research Perspectives on the Worldwide Effects of the Pandemic on Economic and Social Inequality". The event was organized on 19 June 2020 by ZEW Mannheim in cooperation with Università Cattolica del Sacro Cuore di Milano (UniCatt) and the Society for the Study of Economic Inequality (ECINEQ).
Keywords: 330; Coronavirus; Soziale Ungleichheit; Wirkungsanalyse